Pendampingan Pembukuan Akuntansi dan Penyusunan Laporan Keuangan Menggunakan Aplikasi Olsera pada UMKM Pasar Laundry di Jakarta Selatan - Anglaini, Elina; Utami, Mega; Adha, Muhammad Adjie; Damayanti, Prisila (ASOSIASI IDEBAHASA KEPRI, 2025)
The aim of this activity is to offer support in the implementation of bookkeeping and the preparation of financial reports, while also guiding the owners of UMKM Pasar Laundry in utilizing the Olsera application. The results show that the owners of UMKM Pasar Laundry feel assisted in managing their business due to the use of the Olsera application. This support helps business owners operate more effectively and efficiently. Through the guidance provided, the owners of UMKM are able to optimize operations and significantly enhance productivity. Olsera application is a mobile application that can help MSMEs in recording sales or income, as well as expenses and debts/payables digitally. The result is a transaction report along with profit and loss that can be viewed easily and can be uploaded in PDF format. The Olsera application is available free of charge for MSMEs to record transactions, monitor cash flow, monitor business performance, and plan businesses so that they can grow rapidly. The methods used in this community service activity include observation, interviews, discussions and tutorials conducted on December 7, 2024.